Penanaman apotek hidup: menggali potensi tanaman obat dengan pendekatan Islami yang moderat untuk kesejahteraan masyarakat - Nurhardini, Rahma; Ni’mah, Choirun; Nursikin, Mukh; Thowaf, Shofirul; Kurniawan, Riza Aditya (Nur Science Institute, 2024)
One method of cultivating herbal plants is creating a living pharmacy. A living pharmacy involves using land to grow medicinal plants that can be used for daily needs. Some examples of plants that can be cultivated in a living pharmacy are ginger, galangal, turmeric, and lesser galangal. Establishing a living pharmacy boosts the immune system and is an alternative to herbal medicine. This community service initiative aims to educate the residents of Dusun Mranggen about the benefits, planting techniques, maintenance, and utilization of these medicinal plants. The method used is Participatory Action Research (PAR), which combines research and action to raise critical awareness and improve conditions and practices through changes within a specific community. As a result, the community has better understood how to grow and utilize herbal plants. It has successfully used available land around their homes to plant medicinal plants that benefit their health.